2021
DOI: 10.3906/sag-2103-194
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Atrial Fibrosis in Atrial Fibrillation Patients with Three Different Methods

Abstract: BackgroundThe presence of atrial fibrosis has already been known as a risk factor for atrial fibrillation (AF) development. ObjectiveWe aimed to evaluate atrial fibrosis with previously defined three different methods, which were cardiac magnetic resonance imaging (C-MRI), echocardiographic strain imaging, and biomarkers, and show the relationship between these methods, in patients with AF scheduled for cryoballoon ablation. Method30 patients were enrolled. Atrial T1 relaxation durations were measured using C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“… 33 Moreover, changes in serum expression levels of FGF-21 and FGF-23, biomarkers of atrial fibrosis, are of great significance in predicting the occurrence of AF. 34 The serum expression levels of FGF-21 and FGF-23 in AF patients are positively correlated with the degree of atrial fibrosis. 27 , 35 In our present study, the serum expression level of miR-29b-3p in AF patients was negatively correlated with the concentration of FGF-21 and FGF-23.…”
Section: Discussionmentioning
confidence: 97%
“… 33 Moreover, changes in serum expression levels of FGF-21 and FGF-23, biomarkers of atrial fibrosis, are of great significance in predicting the occurrence of AF. 34 The serum expression levels of FGF-21 and FGF-23 in AF patients are positively correlated with the degree of atrial fibrosis. 27 , 35 In our present study, the serum expression level of miR-29b-3p in AF patients was negatively correlated with the concentration of FGF-21 and FGF-23.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Kawamura M. et al (2012) [114] found no discriminatory levels of interleukin-6, high-sensitivity C-reactive protein, BNP, renin, and aldosterone for the 24-month recurrence rate of AF, whereas baseline serum levels of PIIINP > 0.72 U/mL predicted AF relapse. Thus, there is a serious discrepancy between biomarker levels corresponding to the presence of atrial fibrosis confirmed by cardiac magnetic resonance imaging and their discriminatory properties for recurrent AF [115][116][117].…”
Section: Other Biomarkers Of Fibrosismentioning
confidence: 99%
“…Розширення передсердь тісно пов'язане з фіброзом, було показано, що розмір передсердя є важливим фактором ризику розвитку персистуючої ФП [26]. Таким чином, дилатація камер серця і фіброз є двома основними процесами, які беруть участь у структурних змінах у передсердях [11].…”
Section: огляд літературиunclassified